TOMBS OF IMOGIRI KINGS: COMMUNITY PERSPECTIVE IN THEIR RELATIONSHIP OF FUNCTIONAL THEORY - Fadhlinaa Afiifatul Aarifah; Muhammad Izzul Haq Zain (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
This paper discusses the functional analysis that occurred around the Tombs of Imogiri Kings. It is to examine why many people willingly come to the tombs of Imogiri Kings while there are many objects of the tour in Yogyakarta. The purpose of this study was to determine the community's perspective on the tomb and its functions using Malinowski's theory analysis. Malinowski developed a functional theory with the understanding that culture is a standpoint with all the activities carried out actually intended to satisfy a series of instinctual needs of human beings related to human life. This research uses a qualitative method, which is written descriptively. The methods of data collection include field studies such as data collection methods include field studies by direct observation of the symptoms in the tombs of the Imogiri kings, conducting interviews with people involved in tomb activities, conducting participant-observers, following a number of rituals there, and literature study. The results of this study indicate that some community perspectives on the tombs of Imogiri kings that are considered sacred are formed from several factors such as history and mystical stories. This centralization then forms certain cultures and beliefs that have certain functions to fulfill the needs of human instincts as Malinowski's theory.